2015
DOI: 10.1007/s13524-015-0431-0
|View full text |Cite
|
Sign up to set email alerts
|

Immigration Enforcement, Parent–Child Separations, and Intent to Remigrate by Central American Deportees

Abstract: Given the unprecedented increase in the flow of migrants from El Salvador, Guatemala, and Honduras to the United States, this article analyzes the impact of U.S. interior enforcement on parent-child separations among Central American deportees, along with its implications for deportees' intentions to remigrate to the United States. Using the EMIF sur survey data, we find that interior enforcement raises the likelihood of parent-child separations as well as the likelihood that parents forcedly separated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
1
20
0
1
Order By: Relevance
“…Tougher immigration enforcement associated with deportation is also a cause of family separation (Amuedo‐Dorantes & Arenas‐Arroyo, ; Amuedo‐Dorantes, Pozo, & Puttitanum, ). For example, Amuedo‐Dorantes and Arenas‐Arroyo () found that increases in immigration enforcement between 2005 and 2015 raised the likelihood that undocumented mothers lived without their spouses by 20% and the likelihood that Hispanic U.S.‐born children lived without their parents by 19%.…”
Section: Immigrant Familiesmentioning
confidence: 99%
“…Tougher immigration enforcement associated with deportation is also a cause of family separation (Amuedo‐Dorantes & Arenas‐Arroyo, ; Amuedo‐Dorantes, Pozo, & Puttitanum, ). For example, Amuedo‐Dorantes and Arenas‐Arroyo () found that increases in immigration enforcement between 2005 and 2015 raised the likelihood that undocumented mothers lived without their spouses by 20% and the likelihood that Hispanic U.S.‐born children lived without their parents by 19%.…”
Section: Immigrant Familiesmentioning
confidence: 99%
“…Recent studies tend to use the state‐local approach to take advantage of the recent changes in state and local immigration laws. In addition to undocumented immigrants’ labor market outcomes, various other outcomes have been examined, such as the interstate migration patterns of undocumented immigrants and natives, the labor market outcomes of natives, and the educational outcomes and living arrangements of the children of undocumented immigrants (Amuedo‐Dorantes & Arenas‐Arroyo, ; Amuedo‐Dorantes & Bansak, , ; Amuedo‐Dorantes & Pozo, ; Amuedo‐Dorantes, Pozo, & Puttitanun, ; Bohn, Lofstrom, & Raphael, , ; Good, ; Hoekstra & Orozco‐Aleman, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is interesting to note that although the "zero tolerance" immigration policy was cited as an intended deterrent (Hirschfield Davis & Shear, 2018), parent-child separations may be counterproductive to this goal. Parents separated from their children due to immigration enforcement report an intention to return to the United States following deportation with a goal of reuniting with their children (Amuedo-Dorantes, Pozo, & Puttitanun, 2015). In other words, their love for their children motivated the seeking of safety and opportunities in a new country as well as the willingness to face detention to reunify with those separated children.…”
Section: Discussionmentioning
confidence: 99%